2008
DOI: 10.1203/pdr.0b013e318181e07c
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Lipopolysaccharide-Induced Inflammatory Response and Phospholipids Metabolism at the Feto-Maternal Interface by N-Acetyl Cysteine

Abstract: Maternal microbial infections cause adverse fetal developmental outcomes including embryonic resorption, intrauterine fetal death, and preterm labor. Recent studies demonstrated that oxidativestress plays an important role in chorioamniotitis pathogenesis. Herein we investigated the effect of N-acetyl cysteine (NAC) on lipopolysaccharide (LPS)-induced preterm labor and fetal demise in murine model. Lipopolysaccharide exposure at embryonic day 18 demonstrated an increase in the abortion rate and fetal demise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In keeping with the observed elevated expression of Sod3 , which was suggestive of extracellular oxidative stress, mice were first treated with NAC, an extracellular reactive oxygen scavenger. Although accumulation of maternal inflammatory monocytes and macrophages, which might contribute ROS, is not evident in placentas of P. chabaudi AS–infected pregnant B6 mice (17), an NAC treatment approach was rationalized by work in a rat model of LPS-induced preterm labor and fetal demise, which responded positively to NAC pretreatment (54) at the same concentrations used in this study. Contrary to expectations, however, NAC mediated no protective effect in malaria-infected mice, and in fact, appeared to be embryotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the observed elevated expression of Sod3 , which was suggestive of extracellular oxidative stress, mice were first treated with NAC, an extracellular reactive oxygen scavenger. Although accumulation of maternal inflammatory monocytes and macrophages, which might contribute ROS, is not evident in placentas of P. chabaudi AS–infected pregnant B6 mice (17), an NAC treatment approach was rationalized by work in a rat model of LPS-induced preterm labor and fetal demise, which responded positively to NAC pretreatment (54) at the same concentrations used in this study. Contrary to expectations, however, NAC mediated no protective effect in malaria-infected mice, and in fact, appeared to be embryotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…4). Histopathological (Carpentier et al, 2011; Fatemi et al, 2011; Girard et al, 2010) and oxidative stress activity (Paintlia et al, 2008) in the placenta following MIA can disrupt the maternal/placental transfer of nutrients to the fetus leading to transient fetal hypoxia. Carpentier et al (2011) showed evidence consistent with reduced oxygen supply to the fetal brain following maternal LPS administration on gestational day 12.5 in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NAC on lipopolysaccharide (LPS)-induced preterm labor and fetal demise in murine model was investigated. NAC pretreatment abolished these effects of LPS in the placenta [38]. We then investigated the effect of NAC on 4-HNE-induced COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%